PENEGAKAN HUKUM TERHADAP PELANGGARAN KODE ETIK NOTARIS DALAM PEMBUATAN AKTA OTENTIK - Matthew Bias Ferari; Hasim Purba; Suprayitno Suprayitno (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The case of deed forgery by Notary HS in Langkat, North Sumatra, highlights the importance of enforcing the notary code of ethics. On April 1, 2024, the MPWN of North Sumatra issued Decision No. 4/MPWN Prov.03.24 of 2024 declaring a violation of Law No. 2 of 2014 concerning Notary Position. This research discusses the law enforcement mechanism against violations of the code of ethics, factors that influence violations, and efforts to overcome violations of the code of ethics in making authentic deeds. With normative and empirical legal approaches, primary data in the form of questionnaires and secondary data from books, journals, and regulations are analyzed qualitatively. Law enforcement involves MPD, MPW, MKN, and law enforcement agencies with internal factors such as personal ethics and external factors such as economic pressure as causes of violations. Efforts in Medan include strict supervision, strict sanctions, training, and cooperation of legal institutions. Research suggestions include increased inter-agency coordination, continuing education for notaries, and periodic evaluation of law enforcement mechanisms to maintain professional integrity and public trust. Keyword: Law Enforcement, Notary Code of Ethics, Violation, Authentic Deed Abstrak: Kasus pemalsuan akta oleh Notaris HS di Langkat, Sumatera Utara, menyoroti pentingnya penegakan kode etik notaris. Pada 1 April 2024, MPWN Sumut mengeluarkan Putusan No. 84/MPWN Prov.03.24 Tahun 2024 yang menyatakan pelanggaran terhadap Undang-Undang No. 2 Tahun 2014 tentang Jabatan Notaris. Penelitian ini membahas mekanisme penegakan hukum terhadap pelanggaran kode etik, faktor yang memengaruhi pelanggaran, dan upaya penanggulangan pelanggaran kode etik dalam pembuatan akta otentik. Dengan pendekatan hukum normatif dan empiris, data primer berupa kuesioner serta data sekunder dari buku, jurnal, dan regulasi dianalisis secara kualitatif. Penegakan hukum melibatkan MPD, MPW, MKN, serta lembaga penegak hukum dengan faktor internal seperti etika pribadi dan eksternal seperti tekanan ekonomi sebagai penyebab pelanggaran. Upaya di Medan mencakup pengawasan ketat, sanksi tegas, pelatihan, dan kerja sama lembaga hukum. Saran penelitian meliputi peningkatan koordinasi antar lembaga, pendidikan berkelanjutan untuk notaris, serta evaluasi berkala mekanisme penegakan hukum guna menjaga integritas profesi dan kepercayaan masyarakat. Kata kunci: Penegakan Hukum, Kode Etik Notaris, Pelanggaran, Akta Otentik